PERBANDINGAN PEMBELAJARAN METODE DRILL DAN KOMANDO DALAM SERVICE PENDEK BULU TANGKIS SISWA DI SEKOLAH DASAR - Endrawan, I Bagus; Satria, M. Haris (Jurnal Ilmiah Bina Edukasi, 2020)
This study was an experimental study that aims to determine the application method and the method of command drill results in short service badminton game. The subjects were fifth grade students of State Elementary School. Data collection techniques using the "Skills Test Badminton derived from the writings of Frank. M. Verducci. "Data analysis techniques using T-Test, after going through the prerequisite test that is test of normality and homogeneity test. The results showed a very significant improvement. Methods drill an increase of 72.78%, an average increase of 7.28%. Methods of command increased by 48.75%, with an average increase of 4.88%. Based on these descriptions can be concluded that an increase in drill method is greater than the methods of command. Differences increase was 24.03% with an average of 2.40%